Biological Effects of Maslinic Acid on Human Epithelial Cells Used in Tissue Engineering - Ortiz-Arrabal, Olimpia; Chato-Astrain, Jesús; Crespo, Pascual Vicente; Garzón, Ingrid; Mesa-García, María Dolores; Alaminos, Miguel; Gómez-Llorente, Carolina (Frontiers in Bioengineering and Biotechnology, 2022)
In the present work, we evaluated the potential of maslinic acid (MA) to improve currently available keratinocyte culture methods for use in skin tissue engineering. Results showed that MA can increase cell proliferation and WST-1 activity of human keratinocytes after 24, 48 and 72h, especially at the concentration of 5 µg/mL, without affecting cell viability. This effect was associated to a significant increase of KI-67 protein expression and upregulation of several genes associated to cell proliferation (PCNA) and differentiation (cytokeratins, intercellular junctions and basement membrane related genes). When human keratinocytes were isolated from skin biopsies, we found that MA at the concentration of 5 µg/mL significantly increased the efficiency of the explant and the cell dissociation methods. These results revealed the positive effects of MA to optimize human keratinocyte culture protocols for use in skin tissue engineering.